Meta-analysis on the treatment options and outcomes of carotid blood blister aneurysms. (October 2021) - Roy, Anil K.; Lekka, Elvira; Lee, Kyung H.; Choi, Phillip; Day, Arthur L.; Roc Chen, Peng
Highlights: Carotid blister aneurysms can be treated with surgical and endovascular techniques. A trend towards improved outcomes is seen with endovascular techniques. Patient outcomes are similar for different endovascular techniques. Patient outcomes are negatively affected by retreatments. Abstract: Objective: Carotid blister aneurysms remain a formidable surgical challenge with varied surgical options. There have been significant advancements in the endovascular management of these aneurysms with the introduction of flow diverters. The comparative risk profiles for different endovascular options compared to surgical management of these lesions is not completely understood. Methods: The study is a comprehensive systematic review and meta -analysis on the treatment of carotid blood blister aneurysms. Pubmed searches were used to identify relevant articles and patient level data was extracted. Two and three group analyses were conducted comparing surgical and endovascular strategies and surgical, stent coil and flow diversion techniques respectively. Patient outcomes were graded on the modified Rankin Scale with a score of 2 or less defined as favorable. Results: In total, 83 studies (41 and 42 studies on surgical and endovascular interventions, respectively) with 1119 patients met our inclusion criteria. A statistically significant difference (at the 5% level of significance) in the effect among three different interventions was not found (Q = 3.41, p = 0.1815) under the random-effect model. Our results did show summary proportions of favorable outcomes were higher in the stent coil (0.87, 95% CI: 0.79 – 0.94) and flow diversion (0.87, 95% CI: 0.75 – 0.96) than that of surgery (0.76, 95% CI: 0.71 – 0.83). Conclusions: Our results suggest a trend towards improved patient outcomes with endovascular techniques compared to surgical strategies but statistical significance was not achieved. We also found that endovascular techniques compare favorably. Increasing retreatments were found to negatively affect patient outcomes.